PENGEMBANGAN WISATA EDUKASI KONSERVASI PENYU DI PANTAI PASIR JAMBAK KECAMATAN KOTO TANGAH KOTA PADANG - fovi melani danra; Sri Mariya (JURNAL BUANA, 2021)
The purpose of this research are (1) to analyze the potential of educational tourism on the conservation of turtles in Pasir Jambak, (2) to know the development of educational tours for the conservation of sea turtles on the Pasir Jambak beach. This type of research is qualitative. The population and the sample are (1) place, (2) activities, (3) actors. Data collection techniques are observation, interviews, and documentation. The data analysis technique in this research is the Miles and Huberman technique and site analysis. The results of this study are (1) the potential of the pasir jambak beach educational tourism objects which were found to be divided into three groups, first the tourist attractions still come from nature, where this beach is still very beautiful and then has a native turtle habitat, second amenietas is not optimal because it still exists, the facilities that must be added to attract tourists, the third accessibility is quite good because the road is permanent, there are many alternative roads and the condition is also good. (2) based on interviews with tourists, traders, surrounding communities, managers, and tourism experts whose results were analyzed by site analysis, to the development of educational tourism on the conservation of sand jambak beach turtles, the researchers decided that several supporting facilities needed to be added such as children's games, photo spots, information banners, museum, and volley hall.